Engaging libraries and information professionals with the health and medical conditions of the Filipino - Merced, Briccio M., Jr. (2016)
The Filipino is far from pinkish in the 21st century. Genetics, lifestyle, and diseases resulting from environmental exploitation such as dengue, hypertension, cardiovascular, and the alarming rise of HIV-AIDS, have painted a not-so-rosy Filipino in this age and clime based on data from the country's Department of Health. While the government is doing its part in this area, libraries and information professionals can contribute their share by utilizing community engagement principles and practices to mitigate the adverse effects of diseases and illnesses. There are several models and frameworks for the practice of community engagement. Among these are the social ecological model of health, the active community engagement continuum, and the community-based participatory research. Given the role of information managers, libraries and information professionals can engage liberally, moderately, or conservatively with the health and medical conditions of the Filipino.
Keywords: Libraries; Medical conditions; Information centers; Health